Quando a segunda campa toca: a ambiência lúdica do recreio da Escola Estrada Nova como perspectiva para o ensino e aprendizagem em dança - GOMES, Luana Cristina Ribeiro (2018)
This monograph is immersed on the ludical ambience of the students from Estrada Nova School in Belém of Pará, precisely on Pratinha II neighborhood, as a source propulsion of dance local teaching. Developing either from a study based on a cartographic methodology (ROMAGNOLI, 2009) some analisys of the most variety body expressions. LABAN (1978), in constructive dialogues with the authors ANDRADE (2012), DOWBOR (2007) e MARQUES (2007) of educate through dancing practices in the school sphere. This research is based on a estructring of dance laboratories from the ludic to approach dance, school and children’s education close together (ANDRADE, 2013), present in their socio cultural context and doing some possible dialogues for a whole body education, talking about school culture, it’s noticed that they have a freedom expression in small tendences. Considering this, the principal meaning of this monograph is the elaboration of a methodologigal strategies for the dance teaching, inspired by the ludic ambience sound that reverberates right after the second touch: The Break Time.